The Effect of Discipline and Organizational Climate on the Quality of Public Services at the Bogor City Samsat - Triseno Budiharto; Yuni Pratikno; Sitta Kusuma (Dinasti International Journal of Digital Business Management, 2026)
The quality of public service is the main indicator of the success of government agencies' performance in meeting the needs and expectations of the community, especially in motor vehicle administration services at the Bogor City SAMSAT which demands speed, accuracy, and accountability of service. Optimal service quality cannot be separated from the role of human resources, especially work discipline and organizational climate formed in the work environment. This study aims to analyze the influence of work discipline and organizational climate on the quality of public service at the Bogor City SAMSAT, both partially and simultaneously. This study uses a quantitative approach with a survey method. Data were collected by distributing questionnaires to 112 Bogor City SAMSAT employees who served as research respondents. The data analysis technique used was multiple linear regression analysis with the help of the Statistical Package for the Social Sciences (SPSS) version 29 program. The results of the study indicate that partially work discipline has a positive and significant effect on service quality, with a t-value of 9.418 and a significance level of 0.000. In addition, organizational climate also has a positive and significant effect on service quality with a t-value of 5.872 and a significance level of 0.004. Simultaneously, work discipline and organizational climate have a significant effect on the quality of public services, as indicated by the F-value of 45.832 with a significance level of <0.001. The coefficient of determination (R Square) of 0.457 indicates that work discipline and organizational climate are able to explain 45.7% of the variation in service quality, while the remaining 54.3% is influenced by other factors outside the research model. This finding confirms that the implementation of consistent work discipline and the creation of a conducive organizational climate are strategic factors in improving the quality of public services at SAMSAT Bogor City